Lucan's Lost Gauls: The Interpolation at De Bello Civili 1.436-40 - Andrée, Alexander (Classica et Mediaevalia, 2021)
This article discusses five spurious lines at Lucan 1.436-40. Reviewing the early printed tradition of De bello civili as well as examining the medieval manuscripts in which the lines are found, the study explores the extant evidence for the lines. In its search for the origin of the lines, the investigation comprises a discussion of the palaeography of the manuscripts, the poetic and contextual interpretation of the lines, and will venture a suggestion as to their date and presumptive author and the location where they were likely composed.